ANATOMI DELAPAN JENIS KAYU KURANG DIKENAL DARI SUKU FLACOURTIACEAE SAMPAI JUGLANDACEAE (Wood anatomy of eight lesser known wood species of Flacouriiaceae to Juglandaceae) - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1996)
Gross and anatomical features of eight lesser known wood species  belongs to 5 families from Flacourtiaceae to Juglandaceae were observed and described for  identification purposes. Fiber dimension were also measured for  evaluation of their suitability for pulp.  Septate fibers, vessels in radial multiples. some ray longitudinallyfused are the main characters of Homalium and   Trichadenia    (Flacourtiaceae).    Bucklandia    and    Distylium    (Hamamelidaceae)   are characterized by small and polygonal vessel,  scalariform perforation plate, and disjunctive end wall at upright ray cells. Urandra and Platea (Icacinaceae) are characterized by two type of ray  width, fibers  with  distinctly bordered pit,  scalariform  perforation  plate.and  yellowish  wood colour.  Four  species  contain    fibers   with  medium  quality for  pulp   (Engelhardtia  spicata, Bucklandia triscuspis,  Platea  latifolia,   and  Trichadenia  philippinensis).  The rest four  species contain fibers  with poor  quality.  Trichadenia  philippinensis  is the only one among eight wood species examined which has decorative  appearance  :  moderatelyfine  texture,  bright yellow  in colour and considerable high density. It is thereforepossible  to be used as "ramin" substitute.Key words:   wood anatomy,  identification, Flacourticeae, Juglandaceae.